ANALYSIS OF ORGANIZATIONAL PERFORMANCE THROUGH TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE - Sukmo Hadi Nugroho; Elisabeth Tanti Pudiastuti (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Organizational performance plays an important role as a measure of the success of an organization or company. To achieve this success, organizational performance is influenced by many factors, including transformational leadership and organizational culture itself. The purpose of this study was to determine the effect of these two factors on organizational performance. The population of this research is all employees in a company of 94 people with the sampling technique using the total sample. Based on data processing with the SPSS Version 19.00 statistical program, it proves that partial hypothesis testing for transformational leadership and organizational culture variables is proven to affect organizational performance, this explains that the better the leadership and organizational culture are implemented, the more it can improve organizational performance. independent of organizational performance can be seen in the value of R Square of 33.1% and the rest is influenced by other variables not examined in this study. This shows that leadership and organizational culture have an important role for success in motivating employee work, which ultimately has an impact on organizational performance. Keywords: Organizational Performance, Transformational Leadership, Organizational